The Dolor's traslacion ritual as conflict and compromise - Sarmiento, Ramon Felipe A. (Philippine Studies: Historical and Ethnographic Viewpoints)
This article traces the history and meaning of the traslacion or ritual transfer of the Marian image Dolor in Catanduanes province between the origin village and the parish center. In the course of the twentieth century, the location of the image and the control of its devotion have been contested. The ritual first emerged as a compromise between advocates of popular and institutional devotional forms, which eventuated in the full-blown religious procession at present. However, the persistent struggle between the parish center and the village has made the traslacion into an arena for enacting power and the politics of place.